1995
DOI: 10.1111/j.1365-2486.1995.tb00041.x
|View full text |Cite
|
Sign up to set email alerts
|

Productivity and water use of wheat under free‐air CO2 enrichment

Abstract: A free-air CO2 enrichment (FACE) experiment was conducted at Maricopa, Arizona, on wheat from December 1992 through May 1993. The FACE apparatus maintained the COj concentration, [CO2], at 550 jimol mor' across four replicate 25-m-diameter circular plots under natural conditions in an open field. Four matching Control plots at ambient [CO2](about 370 jimol mol"^) were also installed in the field. In addition to the two levels of [COjI, there were ample (Wet) and limiting (Dry) levels of water supplied through… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

28
204
5
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 311 publications
(239 citation statements)
references
References 35 publications
28
204
5
2
Order By: Relevance
“…On the other hand, a major argument against weighting of climate models based on hindcast error is that it assumes that the response to future radiative forcing will be consistent with that in the historical period, which cannot be tested. Crop models on the other hand can at least be tested against field experiments that impose higher atmospheric CO 2 concentrations (Kimball et al 1995;Ewert et al 2002) and higher temperatures (Wall et al 2011) than are observed today.…”
Section: Assigning Different Weights To Each Model In a Multi-model Ementioning
confidence: 99%
“…On the other hand, a major argument against weighting of climate models based on hindcast error is that it assumes that the response to future radiative forcing will be consistent with that in the historical period, which cannot be tested. Crop models on the other hand can at least be tested against field experiments that impose higher atmospheric CO 2 concentrations (Kimball et al 1995;Ewert et al 2002) and higher temperatures (Wall et al 2011) than are observed today.…”
Section: Assigning Different Weights To Each Model In a Multi-model Ementioning
confidence: 99%
“…Extensive controlled-environment experiments such as the Free-Air Concentration Enrichment experiments (e.g., Kimball et al, 1995;Ainsworth et al, 2002;Leakey et al, 2004;Kim et al, 2006Kim et al, , 2007 have showed that increases in both mean and extremes of temperature and elevated [CO 2 ], under predicted climate change scenarios, can impact the growth and development of crops in several ways. Sustained temperature increases over the season will change the growing period of a crop (e.g., IPCC, 2001), whereas short episodes of high temperature during the critical flowering period of a crop can impact yield independently of any substantial changes in mean temperature (e.g., Matsui and Horie, 1992;Wheeler et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…All other effects of elevated [CO 2 ] on plants and ecosystems are derived from these two fundamental responses . Rising CO 2 would increase the photosynthesis rate, especially for C 3 crops (Kimball et al, 1995). Although C 4 crops may not show a direct response in photosynthesis activity, an indirect increase in water use efficiency in water-stressed environments via reduction in stomatal conductance may still increase yield .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations